Participatory mapping with herders in a climate adaptation research project - Ilboudo Nébié, E.K.; West, C.T.; Crane, Todd A. (Society for Applied Anthropology, 2021)
Declining grazing lands threaten the livelihoods of Fulɓe herders in Burkina Faso and other parts of Africa. I used GIS to spatially represent ethnographic narratives about land use and land cover changes. In a place where maps were unavailable or treated as closely held community secrets, I used participatory mapping to offer participants the opportunity to control the process and resulting maps. Our project sought to understand environmental challenges from a fine-grained emic perspective using high-resolution satellite imagery and focus groups. I reflect on challenges of conducting fieldwork in one’s home country, which made it easier to build relationships and interact with officials. At the same time, however, I faced the intersecting challenges of “being an outsider and a woman” as I interacted with Fulɓe men and that of being “too educated” in interacting with women.